RAPID IMPACT ASSESSMENT OF THE SOURCES OF ELECTROMAGNETIC PULSES AND ELECTRIC SPARK DISCHARGE ON SIMULATORS OF BIOLOGICAL TISSUES - Y. T. Al-Ademi; M. V. Davydov; T. A. Pulko; N. V. Nasonova; L. M. Lynkov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Effects of pulsed magnetic field on developed samples of models of biological tissue are examined. Experimental methodology for rapid assessment of stun effects of discharges on replicas of the body, using different types of protective materials, reduces the impact of these discharges is proposed.